Exploring the Role of Community Pharmacists in Obesity and Weight Management in Qatar: A Mixed-Methods Study - Sawsan AlMukdad (8421963) (2021)
Introduction Obesity is a major public health burden in Qatar. Pharmacists can play an important role in providing weight management services (WMSs). This study aimed to explore their attitudes, practice, perceived competence, and role in WMSs in Qatar. Methods A mixed-method explanatory sequential design was applied in the study. A validated online questionnaire was administered followed by qualitative individual and focus group interviews. Results Two-hundred seventy community pharmacists completed the survey (response rate 45%). More than half of them indicated that they often or always explain to patients the risks associated with overweight and obesity (56.2%), recommend weight loss medications, herbs or dietary supplements (52.4%), and counsel about their proper use and/or side effects (56.9%). Conversely, the majority of the pharmacists rarely or never measure patients’ waist circumference (83.8%) or calculate their body mass index (72.1%). Over 80% had very positive attitudes towards their role in weight management. Around three-quarters of the participants agreed or strongly agreed that difficulty in following-up with patients (80.7%), lack of private consultation area (75.7%), and lack of pharmacist’s time (75.2%) are barriers for implementing WMSs. More than 60% stated that they are fully competent in 7 out of 24 WMSs listed. Some themes generated include pharmacist’s role and impact in weight management, need for training about weight management, and impact of social media on patients’ perceptions. Conclusion Qatar community pharmacists reported positive attitudes towards the provision of WMSs. However, they identified several barriers against provision of WMSs. Several strategies are proposed to overcome barriers and to improve the provision of WMSs in community pharmacies in Qatar. Other Information Published in: Risk Management and Healthcare Policy License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.2147/rmhp.s309142